Pengaruh Multimedia Interaktif Berbasis Aplikasi Articulate Storyline 3 pada Materi Sistem Koordinasi Manusia Terhadap Motivasi Belajar Kelas XI MIPA di MAN 1 Kota Makassar - Khairunnisa, Magfirah; Hamansah, Hamansah; Rivai, Andi Tenri Ola (Indo-MathEdu Intellectuals Journal, 2024)
The purpose of this study was to determine the effect of using interactive multimedia based on the articulate storyline 3 application on the human coordination system material for class XI MIPA at MAN 1 Makassar City. The type of research used was quasi-experimental with a non-equivalent control group design. The sampling technique used the purposive sampling method. The results showed that the learning motivation of students who were taught using interactive multimedia based on the articulate storyline 3 application was in the high category with an average value of 66.20. While the learning motivation of students who were taught without using interactive multimedia based on the articulate storyline 3 application was in the high category with an average value of 61.26. The results of the hypothesis test analysis in this study were 0.001 < 0.05 or H0 was rejected and H1 was accepted so that it can be concluded that there is an effect of using interactive multimedia based on the articulate storyline 3 application on student learning motivation on the human coordination system material for class XI MIPA at MAN 1 Makassar City